Pengaruh Profitabilitas, Kebijakan Utang, dan Kebijakan Dividen Terhadap Nilai Perusahaan - Kurniawan, I Gede Eka; Asmara Putra, I Nyoman Wijana (E-Jurnal Akuntansi; Vol 28 No 3 (2019)DO - 10.24843/EJA.2019.v28.i03.p10, 2019)
The purpose of this study is to examine the effect of profitability, debt policy, and dividend policy on firm valueThe sampling method used was purposive sampling with the number of samples obtained was 14 companies. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of the analysis it was found that profitability had a positive effect on firm value. This shows that the higher the profitability, the higher the value of the company. Debt policy does not affect the value of the company. This shows that the high level of debt to equity ratio does not have implications for the high and low value of the company. Dividend policy has a positive effect on company value. This shows that increasing dividend payments will increase the value of the company. Keywords : Profitability, debt policy, dividend policy, company value.